Religious instincts and the transformation of inquiry in Peirce's pragmaticism - Ward, Roger A. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
In this essay I begin by tracking the transformation of Peirce’s notion of inquiry from «The Place of Our Age» to «The Fixation of Belief» which lays the ground for pragmatism. I next trace the movement from pragmatism to pragmaticism via the role of instinct, and then conclude by showing how the content of Peirce’s religious faith and his instinctive love for the church and the reality of God shapes the telos of inquiry, a telos that is evident in the transformation of the inquirer, most poignantly described in «A Neglected Argument for the Reality of God».
Páginas 61-69
Keywords: Pragmatismo; Religión--Filosofía; https://purl.org/pe-repo/ocde/ford#6.03.01